PENGARUH PENGUNGKAPAN DIRI (SELF DISCLOSURE) TERHADAP STRES PADA MAHASISWA YANG MENGERJAKAN SKRIPSI DI FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TEKNOLOGI SUMBAWA - Vivi Fitri Handayani; Ivon Arisanti; Ayuning Atmasari (JURNAL PSIMAWA, 2019)
Students who are working on a thesis are vulnerable to stress. Stress on students who are working on a thesis is caused by problems faced in the process of preparing a thesis such as problems with the supervisor, it is difficult to find research subjects and references that are difficult to find can cause stress. The tendency of students in peer groups to encourage them to do self disclosure to express their thoughts and feelings. This research dimed at knowy the effect of self disclosure on stress in student Faculty of Economy and Bussiness in Sumbawa Univ of Technology. This research used quantitatif descriptive approach. Technique of sampling is purposive sampling, and determining sampling representative use cluster sampling formula there sixty two students are involved in sample. Research data is taken using research instrument namely scala self disclosure and scala stress. To examine of research instrument the writer used constracs validity based on factor analysis. The result of this research showed that there are significant effect between self disclosure on stress and R Square, it is 0,280 by significant 0,000<0,05. Based on result, self disclosure of students on high level it is 41,9%. It showed, stress on students were low, it is 41,3%.